Business not as usual: how multisectoral collaboration can promote transformative change for health and sustainable development. (7th December 2018) - Kuruvilla, Shyama; Hinton, Rachael; Boerma, Ties; Bunney, Ryan; Casamitjana, Nuria; Cortez, Rafael; Fracassi, Patrizia; Franz-Vasdeki, Jennifer; Helldén, Daniel; McManus, Joanne; Papp, Susan; Rasanathan, Kumanan; et al.
Abstract : Shyama Kuruvilla and colleagues present findings across 12 country case studies of multisectoral collaboration, showing how diverse sectors intentionally shape new ways of collaborating and learning, using "business not as usual" strategies to transform situations and achieve shared goals